Pengaruh work stress dan work-life balance terhadap affective commitment dengan job satisfaction sebagai variabel mediasi pada karyawan pt. Subaindo cahaya polintraco - Armunanto, Lola Amalia; Rozaq, Khoirur (Jurnal Ilmu Manajemen, 2024)
This research examines the influence of work stress, work-life balance, and job satisfaction on affective commitment in PT X. This research will discuss the direct impact of work stress and work-life balance on affective commitment and the indirect influence through job satisfaction as a mediation variable. The casualty test and quantitive method are used in this research to test the correlation between the four variables. The purposive technique is used for sampling, with a sample size of 88 employees in PT. X. Data was collected using a statement questionnaire with a scale of 1 to 5 distributed directly. Statistical analysis uses partial least squares (PLS) with SmartPLS 3.2.9 software. The result of this study finds that work stress does not have a significant effect on affective commitment. Work-life balance has a positive and significant effect on affective commitment. Work stress has a positive significant impact on job satisfaction. Work-life balance has a positive significant effect on job satisfaction. Job satisfaction has a positive significant impact on affective commitment. Job satisfaction can mediate the influence of work stress on affective commitment. Job satisfaction can mediate the effects of work-life balance on affective commitment.